Матрица "подполья" в концепции героев позднего Достоевского - Романов, Юрий Александрович (Петрозаводский государственный университет, 2014)
Исследуются архетипические свойства образа человека из «подполья» в образной системе Достоевского: рассмотрены теория архетипов К. Г. Юнга, попытки построения типологии образов Достоевского в русском литературоведении, представлены модель «подпольного» сознания и поведения в главном герое повести Достоевского «Записки из подполья» и ее воплощение в героях «великого пятикнижия» писателя, проанализированы такие составляющие «подпольной» матрицы, как отрицание Божьего мира, человекобожеское мессианство, эстетическая самоказнь, стремление к «подпольному» покою. Сделаны выводы о влиянии архетипического образа человека из «подполья» на последующее творчество не только русских, но и зарубежных классиков.

This article focuses on the study of the archetypal character of “underground” man in Dostoevsky’s character system. The theory of archetypes by C. G. Jung and the attempts to construct Dostoevsky’s character typology in the Russian literary criticism are concerned. The model of “underground” consciousness and behavior, refl ected in the protagonist of Dostoevsky’s “Notes from Underground”, together with its embodiment in the heroes of the writer’s “fi ve great novels” are presented. Such components of the “underground” matrix as the God᾿s world denial, Man-god’s messianism, aesthetic self-torture, pursuit of “underground” peace are analyzed. Conclusions about the infl uence of the archetypal character of the “underground” man on the subsequent works not only of the Russian but also of the foreign classics are made.
Matrix of "underground" in concept of late Dostoevsky’s heroes
Keywords: архетип; Юнг К. Г.; "Записки из подполья"; "великое пятикнижие"; русская литература; Dostoevsky; archetype; Jung C. G.; "Notes from Underground"; "five great novels"